2005
DOI: 10.1038/sj.leu.2403835
|View full text |Cite
|
Sign up to set email alerts
|

DEK-CAN molecular monitoring of myeloid malignancies could aid therapeutic stratification

Abstract: The t(6;9)(p23;q34) is a recurrent chromosomal abnormality observed in 1% of acute myelogenous leukemia (AML), which generates a fusion transcript between DEK and CAN/NUP214 genes. We used a DEK-CAN real-time quantitative (RQ)-PCR strategy to analyze 79 retrospective and prospective samples from 12 patients. Five patients reached DEK-CAN negativity (sensitivity 10 À5 ); all underwent early allogeneic hematopoietic stem cell transplantation (median 5.5 months from diagnosis) with some demonstrating molecular po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 34 publications
3
39
1
6
Order By: Relevance
“…9,10 The current matchedpair analysis of the nationwide survey demonstrated that the OS and the non-relapse mortality, as well as the relapse rate, were independent of the presence of t(6;9)(p23;q34) in allogeneic HSCT recipients, thus suggesting that allogeneic HSCT may be able to overcome the unfavorable effect of t(6;9)(p23;q34) in AML patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The current matchedpair analysis of the nationwide survey demonstrated that the OS and the non-relapse mortality, as well as the relapse rate, were independent of the presence of t(6;9)(p23;q34) in allogeneic HSCT recipients, thus suggesting that allogeneic HSCT may be able to overcome the unfavorable effect of t(6;9)(p23;q34) in AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] The translocation of chromosome (6;9)(p23;q34) forming the DEK/NUP214 fusion mRNA is observed in B1% of AML cases. 9 The characteristics of AML with t(6;9)(p23;q34) are known to include development at a younger age, 10 resistance to chemotherapy and a very poor prognosis. 9 Therefore, the presence of this karyotype in AML patients is an indication for HSCT; however, the impact of t(6;9)(p23;q34) on the outcome of HSCT remains unclear because of the rarity of this entity.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although additional karyotypic aberrations are rare, they may appear during disease progression. 7,9 As a result of the translocation, the 3 0 part of the can gene from chromosome 9q34 is fused to the 5 0 end of the dek gene on chromosome 6p23, resulting in the formation of a chimeric dek/ can fusion gene on the 6p-derivative. The breakpoints on chromosomes 6 and 9 are located in one specific intron on each chromosome.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Given the rarity of this particular subgroup of AML, previous reports attempting to describe the incidence, associated clinical features, and prognosis have been based on small patient cohorts, leaving some uncertainty about the nature of t(6;9) AML. [1][2][3][4] In order to better define this syndrome, a retrospective study of five Cooperative Groups databases (Southwest Oncology Group (SWOG), Cancer and Leukemia Group B (CALGB), Eastern Cooperative Oncology Group (ECOG), Childrens Oncology Group (COG) including the Pediatric Oncology Group (POG) and Children's Cancer Group (CCG)) was conducted.…”
mentioning
confidence: 99%